The Principle of Good Faith in Policy Execution as the Basis for the Legal Protection of the Insured in Life Insurance Contracts - Lulu Syakirah Alatas; Risna Menda Lovinta Siregar (Rechtsvinding, 2026)
The implementation of life insurance policies often leads to legal disputes concerning the application of the principle of utmost good faith and the legal protection of insured parties. Claim rejections are frequently based on the alleged failure of insured parties to disclose material facts, although insurers are likewise required to provide transparent information, conduct proper risk assessment, and perform contractual obligations in good faith. This study aims to analyze the principle of good faith as the legal foundation for protecting insured parties in the implementation of life insurance policies and to examine its role in resolving insurance disputes. The research employs a normative legal method using statutory, conceptual, and case approaches. Primary legal materials consist of the Indonesian Civil Code, the Indonesian Commercial Code, Law Number 40 of 2014 concerning Insurance, and relevant court decisions, supported by secondary legal materials collected through library research. The materials were analyzed qualitatively using a prescriptive approach. The findings reveal that the principle of good faith creates reciprocal obligations for both insurers and insured parties throughout policy implementation, including disclosure of material facts, professional underwriting, transparent policy formulation, and objective claim assessment. The study concludes that consistent application of this principle strengthens legal certainty, promotes balanced contractual relationships, and enhances legal protection for insured parties in life insurance practice.